2005
DOI: 10.1038/sj.ijo.0803129
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, lipoproteins, lifestyle, adiposity and fat-free mass during middle age: the Fels Longitudinal Study

Abstract: Introduction: Although lipid profiles tend to worsen with age, it is not fully known if such age-related changes are influenced primarily by body composition and lifestyle or by other aspects of aging. Objective: We investigated the extent to which the fat and fat-free components of body mass index (BMI) and lifestyle factors influence patterns of change in lipids independent of age. Design: Serial data were analyzed using sex-specific longitudinal models. These models use serial data from individuals to assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
73
8
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 41 publications
11
73
8
3
Order By: Relevance
“…The low HDL-C level was expected as respondents were among those who are overweight and obese and studies have shown that HDL-C has an inverse correlation with BMI. 11,12 Studies have shown that those with higher level of physical activity would have lower TC, LDL-C, TG and FBS, but higher HDL-C, however in this study the only significant differences between the two groups at baseline was for TG (i.e. TG was significantly lower in the 'high to moderate level' physical activity group compared to 'low level' physical activity group).…”
Section: Discussioncontrasting
confidence: 65%
“…The low HDL-C level was expected as respondents were among those who are overweight and obese and studies have shown that HDL-C has an inverse correlation with BMI. 11,12 Studies have shown that those with higher level of physical activity would have lower TC, LDL-C, TG and FBS, but higher HDL-C, however in this study the only significant differences between the two groups at baseline was for TG (i.e. TG was significantly lower in the 'high to moderate level' physical activity group compared to 'low level' physical activity group).…”
Section: Discussioncontrasting
confidence: 65%
“…The relationship between HDL cholesterol and BMI is accounted for by FFMI. In a longitudinal study (Schubert et al, 2006) of adults, increase in FFMI without accompanying decrease in FMI was associated with a decrease in HDL cholesterol. In the growing child the relationship of changes in FMI and FFMI with lipid profile needs to be further explored.…”
Section: Discussionmentioning
confidence: 89%
“…Associations between menopause or AAM and CRF could be largely confounded by chronological age [8][9][10][11] and daily lifestyle, such as body weight, smoking, alcohol consumption, or physical activity [10][11][12] . Chronological age and lifestyle are recognized as influential factors on CRF 1,13) and are mutually correlated 14,15) .…”
Section: Natural Menopause Status and Age At Menopausementioning
confidence: 99%